Level of Bank Health, Growth Rate and Banking Value in Indonesia - Budi Prajogo; Etty Murwaningsari (Jurnal Riset Akuntansi Terpadu, 2022)
This study aims to explore the soundness, growth rate and value of banking in Indonesia. This study also compares the level of soundness, growth rate and value of Islamic banks and conventional banks. This research is interesting and important to do, because as a country with the largest Muslim population in the world, the Islamic banking sector is the main solution to help the economy in an Islamic way. However, the use of Islamic banking services by the public is still not optimal. Meanwhile, Islamic banks are proven to be able to survive the global economic crisis. The motivation underlying this research is that different perspectives in the management of the two types of banks affect the level of bank resilience in facing the crisis. It is proven that when there is a global crisis, Islamic banks are more resistant to testing and survive. This study examines the development of corporate governance in an in-depth Islamic perspective for Islamic commercial banks and compares it with corporate governance in conventional banks. The Islamic context in doing business is very different from the conventional business context. Therefore, it needs to be developed separately based on the concepts of monotheism. The research provides input for the development of models for the application of Islamic Corporate Governance. Another benefit in this study is the level of public acceptance of Islamic banking services, which are carried out. The research output is an empirical model for developing the Islamic Corporate Governance index. The research provides additional input for similar research that are still theoretically reviewing.